2018
DOI: 10.1002/rra.3358
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of coarse‐resolution rapid methods for assessing fish passage at riverine barriers: ICE and SNIFFER protocols

Abstract: Man-made barriers have led to river fragmentation, restricting fish migrations to critical habitat. Fragmentation is relevant to the Water Framework and Habitats (Annex II fish) Directives of the European Union. SNIFFER (Water Framework Directive 111) is a United Kingdom-developed fish passability assessment method with passability scores based on published data describing the physiological abilities of different fish species/life stages. SNIFFER is an objective protocol, but final scores require assessor opin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 37 publications
0
14
0
7
Order By: Relevance
“…Since the context of our study was from a longitudinal connectivity restoration viewpoint, particularly as regards fish passage, we recorded obstacles that had the potential to limit upstream movement of fish at normal to low flows (~Q 50 –Q 90 ), while acknowledging that maintaining free downstream‐migration passage is also important (Silva et al , 2018). Obstacles to the free movement of fishes depend on obstacle characteristics (especially height and gradient), fish species and environmental conditions (Kemp and O'Hanley, 2010; Barry et al ., 2018). In our surveys, any artificial structure having a vertical or steeply sloping (>45°) step, exceeding 0.2 m in height, was regarded as a potential obstacle to weakly swimming taxa (Utzinger et al , 1998; Tummers et al , 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Since the context of our study was from a longitudinal connectivity restoration viewpoint, particularly as regards fish passage, we recorded obstacles that had the potential to limit upstream movement of fish at normal to low flows (~Q 50 –Q 90 ), while acknowledging that maintaining free downstream‐migration passage is also important (Silva et al , 2018). Obstacles to the free movement of fishes depend on obstacle characteristics (especially height and gradient), fish species and environmental conditions (Kemp and O'Hanley, 2010; Barry et al ., 2018). In our surveys, any artificial structure having a vertical or steeply sloping (>45°) step, exceeding 0.2 m in height, was regarded as a potential obstacle to weakly swimming taxa (Utzinger et al , 1998; Tummers et al , 2016).…”
Section: Methodsmentioning
confidence: 99%
“…A gravel trap installed at Blackboys Bridge ( Figure 1) is a vertical impediment to upstream fish migration which has a Deniltype fish pass installed. This trap, as well as the Annacotty weir, was recorded as "impassable" to sea lamprey, in the prevailing conditions at the time of study, in a WFD SNIFFER (2010) fish passage assessment (Barry, Coghlan, Cullagh, Kerr, & King, 2018). The Annacotty weir is the most significant structure that may impede sea lamprey passage in this system, however, within 2 km upstream of this structure, migrants also encounter a crump weir fish counter and the remnants of a weir breached to permit sediment transport and fish passage.…”
Section: Study Sites and Selection Of Sampling Locationsmentioning
confidence: 99%
“…Two major weirs are present in the lower part of the main stem. Clondulane Weir is located 25 km upstream of the tidal limit (between MBW09 and MBW10; Note that MBW11 and MBW 12 are at the tidal limit hydraulic head difference of 2.5 m. Both structures were assessed as "Impassable" to sea lamprey in the prevailing conditions, using the SNIFFER (2010) or WFD 111 protocol (Barry et al, 2018). Evidence from previous spawning surveys has indicated significant P. marinus spawning effort downstream of both structures (Inland Fisheries Ireland, 2010; King & Linnane, 2004) and has shown that some degree of passage upstream of the first weir (Clondulane) can occur in years with higher flows (King & Linnane, 2004;IFI, unpublished data…”
Section: Study Sites and Selection Of Sampling Locationsmentioning
confidence: 99%
See 1 more Smart Citation
“…River fragmentation by small engineered structures, far more numerous than dams, has led to severe declines or local extinctions of many fish populations by blocking upstream movements for reproduction, feeding, and refuge needs [1][2][3]. By identifying the importance of aquatic connectivity for good ecological quality in rivers, the European Water Framework Directive (WFD) emphasized the need to re-establish free movements for all fish species and size classes, regulating that member states should assess all instream obstacles, even small weirs, and minimize their barrier effect [4][5][6]. Since then, a few studies on small obstacles (considering assessment protocols, e.g., [7][8][9], or field assessments, e.g., [10][11][12]) and projects, such as the European project AMBER and other operational programs like the EU LIFE programs, have been developed, aiming to enhance the knowledge on permeability of small obstacles and fish passage, recommend strategies for action, and rehabilitate river habitats [3,13,14].…”
Section: Introductionmentioning
confidence: 99%